The effectiveness on addition of vitamins as an antioxidant in sperm cryopreservation of catfish Clarias gariepinus - Maulana, Fajar; Alimuddin, Alimuddin; Sudrajat, Agus Oman; Setiawan, Dicky; Fahrezi, Muhammad Syifa; Rahmi, Kurnia Anggraini (Jurnal Akuakultur Indonesia, 2026)
One of the problems faced in catfish hatcheries is that the reproductive cycle does not occur throughout the year, so that available male broodstocks with mature gonads are rare. Cryopreservation is a method of storing spermatozoa with the help of diluents and cryoprotectants in frozen conditions to maintain the quality of spermatozoa. Cryopreservation has a negative effect due to the influence of reactive oxygen species (ROS) which causes a decrease in the quality of spermatozoa. An alternative that can be done is using antioxidants in the form of vitamin C and cryoprotectants such as vitamin E. This research aims to test the effectiveness of adding vitamin E and vitamin C to catfish (Clarias gariepinus) sperm on post-cryopreservation sperm quality. The test fish were catfish that had mature gonads and were injected with the ovaprim hormone for final approval. This study consisted of eight treatments and three replications, namely control (fresh sperm), DMSO 10%, DC1 (vitamin C dose 1 mg/mL), DC2 (vitamin C dose 2.5 mg/mL), and DC3 (vitamin C dose 4 mg/mL), DMSO 10%, DE 1 (vitamin E 2 mg/mL), DE2 (vitamin E 4 mg/mL), DE3 (vitamin E 6 mg/mL). The parameters observed include sperm motility, sperm viability, degree of egg fertilization, and degree of egg hatching. Sperm cryopreservation is carried out for one hour. The results showed that the motility, viability, and degree of egg fertilization in the vitamin C and vitamin E treatments were lower (P